IMPROVING ENGLISH LANGUAGE SKILLS OF YOUTH THROUGH THE "DOLZARB 90 KUNLIK" PROGRAM - Nazirova Minavar Anvarbekovna, (TADQIQOTLAR, 2026)
Abstract English  has  become  one  of  the  most  important  languages  for  education, employment,  and  international  communication.  In  Uzbekistan,  various  educational reforms have been introduced to improve young people's foreign language skills. One such initiative is the "Dolzarb 90 Kunlik" (Relevant 90-Day Program), which aims to engage youth in productive educational activities during the summer period. This study examines  the  effectiveness  of  teaching  English  through  the  "Dolzarb  90  Kunlik" program.  The  research  follows  the  IMRAD  structure  and  analyzes  the  impact  of intensive  English  instruction  on  learners'  language  proficiency,  motivation,  and communication  skills.  The  findings  indicate  that  structured  short-term  programs significantly improve students' confidence, vocabulary, and speaking ability.